The complete design in the composite face paradigm: role of response bias, target certainty, and feedback - Meinhardt, Günter; Meinhardt-Injac, Bozana; Persike, Malte (Frontiers in Human Neuroscience, 2014)
Some years ago an improved design (the “complete design”) was proposed to assess the composite face effect in terms of a congruency effect, defined as the performance difference for congruent and incongruent target to no-target relationships (Cheung et al., 2008). In a recent paper Rossion (2013) questioned whether the congruency effect was a valid hallmark of perceptual integration, because it may contain confounds with face-unspecific interference effects. Here we argue that the complete design is well-balanced and allows one to separate face-specific from face-unspecific effects. We used the complete design for a same/different composite stimulus matching task with face and non-face objects (watches). Subjects performed the task with and without trial-by-trial feedback, and with low and high certainty about the target half. Results showed large congruency effects for faces, particularly when subjects were informed late in the trial about which face halves had to be matched. Analysis of response bias revealed that subjects preferred the “different” response in incongruent trials, which is expected when upper and lower face halves are integrated perceptually at the encoding stage. The results pattern was observed in the absence of feedback, while providing feedback generally attenuated the congruency effect, and led to an avoidance of response bias. For watches no or marginal congruency effects and a moderate global “same” bias were observed. We conclude that the congruency effect, when complemented by an evaluation of response bias, is a valid hallmark of feature integration that allows one to separate faces from non-face objects.